Indonesian Muslimah in Realizing Religious Moderation in the Digital Age - Edy Sutrisno (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2023)
Religious moderation is closely related to tolerance, tolerance in Indonesia is never separated from the role of women, women have many contributions in social life through digital space, especially in preventing radicalism. The purpose of this paper is to find out the role of women in realizing religious moderation in the digital era. The method used is qualitative with a literature study approach. The results of this discussion state that women have a major role in building and maintaining the various kinds of tolerance that Indonesia needs. The role of women in realizing religious moderation can be seen; First, women as mothers and wives always reap the seeds of peace and justice. Second, women also play a role as community members who always plant the seeds of peace in society. Third, millennial women always actively participate in campaigning for justice, tolerance and peace on social media so that cases of degrading things that are different from women can be minimized with content that educates the virtual world community where the majority of Indonesian people always surf on social media every day.